ANALISIS INFLASI DAN KURS TAHUNAN DALAM MELIHAT KONDISI RIIL EKSPOR KOPI INDONESIA DI 5 (LIMA) NEGARA UNI EROPA - Leni Panca Mustika Sari; Ihwan Satria Lesmana; Risma Eka Desiyani (Universitas Bina Bangsa, 2022)
This research aimed to analyze annual inflation and exchange rates in view of the real condition of Indonesian coffee exports in 5 (five) European Union Countries (Belgium, France, Germany, Italy, and Netherlands) in 2016-2019. This research method with a qualitative approach and uses secondary data. The results of this study is, inflation condition in Indonesia and 5 (five) European Union Countries using the formula for calculating the consumer price index in 2016-2019 is Indonesia’s average annual inflation of 3,12% and the annual average inflation of 5 (five) European Union Countries at 1,5% and classified into the type of mild inflation.The condition of the annual axchange rate in export activities is a type of exchange rate pegged to the Dollar/USD and tends to fluctuate. Indonesia’s low inflation and rising exchange rate cuase the volume and value of exports to increase and when the highest exchange rate occurs, it causes a decrease in the volume and value of coffee exports in 5 (five) European Union Countries